Overcoming hurdles to intervention studies with autistic children with profound communication difficulties and their families. (August 2021) - McKinney, Ailbhe; Weisblatt, Emma JL; Hotson, Kathryn L; Bilal Ahmed, Zahra; Dias, Claudia; BenShalom, Dorit; Foster, Juliet; Murphy, Suzanne; Villar, Sofía S; Belmonte, Matthew K
Autistic children and adults who are non-verbal/minimally verbal or have an intellectual disability have often been excluded from Autism Spectrum Disorder research. Historical, practical and theoretical reasons for this exclusion continue to deter some researchers from work with this underserved population. We discuss why these reasons are neither convincing nor ethical, and provide strategies for dealing with practical issues. As part of a randomised controlled trial of an intervention for children with profound autism, we reflected as a multi-disciplinary team on what we had learnt from these children, their families and each other. We provide 10 strategies to overcome what appeared initially to be barriers to collecting data with this population. These hurdles and our solutions are organised by theme: interacting physically with children, how to play and test, navigating difficult behaviours, selecting suitable outcome measures, relating with parents, managing siblings, involving stakeholders, timing interactions, the clinician's role in managing expectations, and recruitment. The aim of this article is to provide researchers with the tools to feel motivated to conduct research with children with profound autism and their families, a difficult but worthwhile endeavour. Many of these lessons also apply to conducting research with non-autistic children with intellectual disabilities. Lay abstract: Autistic children who speak few or no words or who have an intellectual disability are the most in need of new understandings and treatments, but the most often left out of the research that can bring these benefits. Researchers perceive difficulties around compliance with instructions, testing, challenging behaviours and family stress. Although research with these children can indeed be difficult, their continuing exclusion is unethical and unacceptable. Drawing on our experiences testing a possible treatment for children with profound autism, we provide 10 practical guidelines related to (1) interacting physically, (2) combining play and testing, (3) responding to challenging behaviour, (4) finding suitable tests, (5) relationships with parents, (6) relationships with siblings, (7) involving stakeholders, (8) planning the testing times, (9) the role of the clinical supervisor and (10) recruiting and retaining participants. We hope that these guidelines will prepare and embolden other research teams to work with profoundly autistic children, ending their historical exclusion from research. These guidelines also could be useful for conducting research with children with intellectual disabilities.